Formação de professores e a desinformação: análise e compreensão de informações midiáticas - SANTOS, Igor Pereira dos (Universidade Federal do Oeste do Pará, 2024)
The phenomenon of disinformation is one of the major problems that humanity has been facing in this last period of society, the era of digital technologies is the great driver of this phenomenon, which together with post-truth and the historical period of post-modernity have been giving support to that this situation becomes increasingly worse. Therefore, the present study seeks to investigate the development of teaching and learning environments in initial teacher training that aim to analyze and understand media information in the face of disinformation. The methodological path is qualitative and exploratory research, with a set of activities being developed as educational guidance in order to collaborate with the initial teacher training process, with regard to the relationship between misinformation and its inferences in society. This set of activities was applied, in a preliminary way, with 14 undergraduate students from the degree course in educational information technology at the Federal University of Western Pará (Ufopa), as a way of analyzing the feasibility and development of the activities. The following instruments were used to organize and process information: questionnaires, field diary and also a group interview. The final results show that the initial teacher training environment is still unable to encompass the complexity of the situation in which misinformation is found, however, it is considered to be the most favorable environment to propagate the skills for tackling misinformation, of which education It is vitally important to deal with this process, being one of the pillars of conflict, and it is necessary to expand studies on this topic.